2022
DOI: 10.2147/copd.s339498
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Noninvasive Ventilation on Diaphragm in Chronic Respiratory Failure

Abstract: Purpose Home non-invasive ventilation (NIV) is recommended in patients with COPD and hypercapnic chronic respiratory failure (HCRF). The mechanism by it can improve alveolar ventilation during spontaneous breathing is not yet completely explained. Our aim is to evaluate the impact of on diaphragm muscle function in a series of patients with HCRF. Patients and Methods Observational, longitudinal, prospective study of a series of patients with very severe chronic obstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Although we could not find comparable data from the literature, our data are supported by observing the significant impact on reduced survival when there is an inadequate response to NIV therapy 9 . On the other hand, successful LTH-NIV is associated with a reduction in paCO 2 values and a drop in bicarbonate concentration 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not find comparable data from the literature, our data are supported by observing the significant impact on reduced survival when there is an inadequate response to NIV therapy 9 . On the other hand, successful LTH-NIV is associated with a reduction in paCO 2 values and a drop in bicarbonate concentration 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of chronic non-invasive ventilation (NIV) on diaphragm function remains underexplored. While some Authors suggest potential improvements in diaphragmatic contraction with NIV, other studies report no discernible effects [ 55 ]. The impact of NIV on patient survival remains controversial.…”
Section: The Diaphragm In the Lung Transplantation Processmentioning
confidence: 99%
“…17 24 A study from 2022 of 30 patients with COPD on non-invasive ventilation for a year showed an improvement in the thickening fraction of the diaphragm with a statistically significant change in hyperinflation indices, perhaps indicating improved function of the diaphragm. 25 Figure 2 briefly summarises the pathophysiology of hyperinflation and potential salutary effects of non-invasive ventilation.…”
Section: Open Access Open Accessmentioning
confidence: 99%